The Attitude of Work-Oriented and Family-Oriented Chinese Women Toward the Evaluations Based on the Traditional Positive Stereotype That Women Are Virtuous - Song, Jingjing; Li, Junnan; Liu, Yanfen; Ruan, Yifan (Frontiers in Psychology, 2021)
Perceivers have contradictory attitudes to the positive stereotypical evaluation. The current study focused on female's attitudes towards positive stereotypical evaluation of virtuous, we further tried to find the boundary conditions and internal mechanisms of female's rejection of virtuous positive stereotyping. Two experimental studies were conducted. In study one, from the perspective of observer, the participants were asked to randomly evaluate one of the three type of female target which correspond the group positive stereotype evaluation, individual positive stereotype evaluation and control group respectively. “The likeability to the target" and "willingness to be a woman like the target" were used to refer to the participants’ attitude to the positive stereotyping evaluation of virtuous. In study two, from the perspective of actor, participants were asked to imagine a situation that the male partner assigned different task to them, and they were randomly been assigned into group positive stereotype evaluation, individual positive stereotype evaluation and control group. “The likeability to the male partner” was used to refer to the participants’ attitude of the positive stereotype evaluation. The results showed that only the work-oriented female would reject the virtuous positive stereotypical evaluation. Participants perceived the virtuous evaluation as family-role requirement, and thus lead to them dislike this positive stereotyped evaluation, thus, the mediation role of family-role perception was supported. But, the mediation role of sense of being depersonalized and competence evaluation were not supported. In general, the virtuous positive stereotypical evaluation always indicates the family-oriented, and thus work-oriented female would reject this stereotypical evaluation.